2018
DOI: 10.1029/2018jg004556
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Controls, Emergent Scaling, and Predictions of Greenhouse Gas (GHG) Fluxes in Coastal Salt Marshes

Abstract: Coastal salt marshes play an important role in mitigating global warming by removing atmospheric carbon at a high rate. We investigated the environmental controls and emergent scaling of major greenhouse gas (GHG) fluxes such as carbon dioxide (CO 2 ) and methane (CH 4 ) in coastal salt marshes by conducting data analytics and empirical modeling. The underlying hypothesis is that the salt marsh GHG fluxes follow emergent scaling relationships with their environmental drivers, leading to parsimonious predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 138 publications
8
46
1
Order By: Relevance
“…Our data show a direct and strong relationship between the levels of dissolved methane, organic matter content and water temperature, as it has been observed in other brackish coastal wetlands (Welti et al, 2017). Methanogenesis is substantially driven by temperature (Martin and Moseman-Valtierra, 2017) and it is therefore the most dominant environmental driver of CH 4 emissions in wetlands (Yvon-Durocher et al, 2014) specifically in coastal salt marshes (Abdul-Aziz et al, 2018). The overall pattern found here therefore suggests a methanogenesis control by temperature in the sediment, which has been described as muddy with numerous stems and roots and scarce micro-fauna (Ruiz et al, 2004).…”
Section: Sources Of Ch 4 In Doñana Salt Marshessupporting
confidence: 79%
See 2 more Smart Citations
“…Our data show a direct and strong relationship between the levels of dissolved methane, organic matter content and water temperature, as it has been observed in other brackish coastal wetlands (Welti et al, 2017). Methanogenesis is substantially driven by temperature (Martin and Moseman-Valtierra, 2017) and it is therefore the most dominant environmental driver of CH 4 emissions in wetlands (Yvon-Durocher et al, 2014) specifically in coastal salt marshes (Abdul-Aziz et al, 2018). The overall pattern found here therefore suggests a methanogenesis control by temperature in the sediment, which has been described as muddy with numerous stems and roots and scarce micro-fauna (Ruiz et al, 2004).…”
Section: Sources Of Ch 4 In Doñana Salt Marshessupporting
confidence: 79%
“…The overall pattern found here therefore suggests a methanogenesis control by temperature in the sediment, which has been described as muddy with numerous stems and roots and scarce micro-fauna (Ruiz et al, 2004). In addition, vegetation in the marshes may have supported a methanogens population that could contribiute to an increase of CH 4 concentrations during warmer conditions, which has been found in Spartina dominated wetlands (Burke et al, 2002;Abdul-Aziz et al, 2018). The organic-matter rich sediment in conjunction with the organic inputs from the heterotrophic Guadalquivir estuary (Flecha et al, 2015) and those generated in situ by the phytoplankton productivity, as indicated by the association found between Chl a and DOC, provide optimal conditions for sedimentary methanogenesis to proceed, with temperature acting as a major regulating driver.…”
Section: Sources Of Ch 4 In Doñana Salt Marshessupporting
confidence: 50%
See 1 more Smart Citation
“…The complexity of the salt marsh response may also be related to tidal forcing, which is a control on water availability and solute content that exists in salt marshes, but not terrestrial upland ecosystems or even most wetlands. In salt marshes, rates of productivity and GHG fluxes vary between high and low tides (Abdul-Aziz et al, 2018;Kathilankal et al, 2008;Moffett et al, 2010) and between the neap and spring tide astronomical extremes (Guo et al, 2009;Tong et al, 2013;this study). Therefore, the carbon cycling response of salt marshes to precipitation change likely depends on tidal context, with a given precipitation change potentially having different or even opposite effects depending on local tidal inundation regime and tidal phase.…”
Section: Ecosystem Responses To Precipitation Change and Their Driversmentioning
confidence: 91%
“…The seasonal change of daytime CO 2 uptake by wetland plants is mainly driven by temperature, photosynthetically active radiation, and day‐length (Moseman‐Valtierra et al, ). Previous studies reported that higher ambient temperature and light intensity could accelerate the activity of the primary C 4 photosynthetic enzyme (RuBisCO), resulting in higher CO 2 uptake (Abdul‐Aziz et al, ; Guo et al, ; Inglett et al, ). Moreover, methanogenesis is substantially driven by temperature (Martin & Moseman‐Valtierra, ), which could contribute to higher CH 4 emission during high temperatures.…”
Section: Discussionmentioning
confidence: 99%